2022
DOI: 10.24925/turjaf.v10i12.2446-2452.5535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation from Rural to Urban Scale for the Effect of NDVI-NDBI Indices on Land Surface Temperature, in Samsun, Türkiye

Abstract: In this study, in order to evaluate the change of LST from rural to urban scale in 20 years, a zoonal statistical analysis was performed by separating the urban and rural districts located on the coastline. Algorithms were applied to the raw data of Landsat 8 and Landsat 7 satellite images, using the Arc Gis 10.2 and Q Gis 3.16 utilities. In this way, NDVI, NDBI and LST data were compared and evaluated in terms of rural and urban districts. The correlation coefficient between the parameters was calculated. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…These results are important in terms of showing that vegetation areas decreased according to NDVI and SAVI calculations, water-covered areas decreased according to mNDWI calculations, and built areas increased according to NDBI calculations. The results of the negative and positive relationships of NDVI and NDBI with LST are in parallel with many studies in the literature (Chen & Zhang, 2017;Ranagalage et al, 2017;Malik et al, 2019;Jamei et al, 2019;Shahfahad et al, 2020;Halder et al, 2021;Yamak et al, 2021;Alademomi et al, 2022;Değerli & Çetin, 2022). The negative relationship between SAVI and LST also supports the study results of Akyürek (2020).…”
supporting
confidence: 88%
“…These results are important in terms of showing that vegetation areas decreased according to NDVI and SAVI calculations, water-covered areas decreased according to mNDWI calculations, and built areas increased according to NDBI calculations. The results of the negative and positive relationships of NDVI and NDBI with LST are in parallel with many studies in the literature (Chen & Zhang, 2017;Ranagalage et al, 2017;Malik et al, 2019;Jamei et al, 2019;Shahfahad et al, 2020;Halder et al, 2021;Yamak et al, 2021;Alademomi et al, 2022;Değerli & Çetin, 2022). The negative relationship between SAVI and LST also supports the study results of Akyürek (2020).…”
supporting
confidence: 88%
“…5 a, b, c). The NDBI index is used to assess the level of urban development in the study area, the NDBI values increase as the built-up area increases and decreases when the built-up area decreases [Degerli, Çetin, 2022]. In 1992, the NDBI value ranged from -0.96 to +0.78 (Fig.…”
Section: The Ndvi and Ndbimentioning
confidence: 99%
“…Numerous studies have indicated that bare soil and impervious surfaces are crucial factors inf luencing UHI, while vegetation and water surfaces can mitigate UHI formation (Song et al, 2014). Many researchers have explored the relationship between LST and built-up areas (Normalized Difference Built-up Index -NDBI) and vegetation (The Normalized Difference Vegetation Index -NDVI) indices (Chen et al, 2014;Guha et al, 2017;Değerli & Çetin, 2022;Alademomi et al, 2022;Haji et al, 2023). Research has confirmed the exceptional correlation between NDVI and LST, as well as between LST and NDBI.…”
Section: Introductionmentioning
confidence: 99%